Load-bearing cement brick with masson pine leaves as filler - XIE HAILIAN (2017)
The invention discloses a load-bearing cement brick with masson pine leaves as filler. The load-bearing cement brick comprises the masson pine leaf filler, natural sand and cement. The cement brick has the technical characteristics that the masson pine leaves uniformly filling the cement brick are granular; masson pine leaf granules are mixed with cement mortar through stirring; and a basic ratio of the masson pine leaf granules to the natural sand to the cement is 25: 25: 25. The load-bearing cement brick provided by the invention has the following beneficial effects: 1, the load-bearing cement brick has the characteristics of environment friendliness, heat preservation, sound insulation, light weight, conservation of materials, low production and application cost (because the masson pine leaves are an easily-available processing-free natural fine material and only needs cutting), etc.; 2, the load-bearing cement brick overcomes the problems that bonding between a conventional cement brick and coating mortar